2011
DOI: 10.1017/s0033291711000018
|View full text |Cite
|
Sign up to set email alerts
|

Are bipolar II patients cognitively impaired? A systematic review

Abstract: Background. There is evidence that bipolar disorder (BD) is associated with significant neurocognitive deficits and this occurs in individuals with BD type I (BD I) and with BD type II (BD II). Only a few studies have focused on cognitive impairment in BD II. The aim of this study was to describe the pattern of cognitive impairment in patients with BD II, in order to identify specific cognitive deficits that distinguish BD II from BD I patients as well as from healthy subjects.Method. We performed a systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 49 publications
2
45
1
1
Order By: Relevance
“…The neuropsychological literature in patients with bipolar I disorder (BP I) demonstrates impairment during the performance of executive control tasks that is pervasive across all mood states (Malhi et al, 2004(Malhi et al, , 2007Martinez-Aran et al, 2004;Henry et al, 2013). Within the domain of executive function, there is evidence of cognitive dysfunction in subjects with bipolar disorder (BP) specifically during the performance of tasks requiring response inhibition (Martinez-Aran et al, 2004;Swann et al, 2009a;Sole et al, 2011;Xu et al, 2012;Henry et al, 2013). Impairment in inhibitory control performance has been observed in subjects with bipolar disorder during mania and euthymia, and it has been shown to be a significant predictor of functional outcomes, including disability severity, quality of life and occupational functioning (Swann et al, 2009b;Reinares et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The neuropsychological literature in patients with bipolar I disorder (BP I) demonstrates impairment during the performance of executive control tasks that is pervasive across all mood states (Malhi et al, 2004(Malhi et al, , 2007Martinez-Aran et al, 2004;Henry et al, 2013). Within the domain of executive function, there is evidence of cognitive dysfunction in subjects with bipolar disorder (BP) specifically during the performance of tasks requiring response inhibition (Martinez-Aran et al, 2004;Swann et al, 2009a;Sole et al, 2011;Xu et al, 2012;Henry et al, 2013). Impairment in inhibitory control performance has been observed in subjects with bipolar disorder during mania and euthymia, and it has been shown to be a significant predictor of functional outcomes, including disability severity, quality of life and occupational functioning (Swann et al, 2009b;Reinares et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis reported that the data concerning psychomotor speed and verbal and visual memory are contradictory and the impairment probably small in magnitude, while on the contrary the data are relatively robust concerning the presence of a working memory defi cit and a decrease of cognitive fl exibility and impaired inhibitory control in BD-II. Also BD-II patients were impaired in recognizing emotions (Sole et al 2011 ). Overall, the literature supports that in quantitative terms, BD-II does not differ much from BD-I (Arts et al 2011 ) although it seems that the prevailing opinion is that BD-II patients perform better than BD-I but worse than healthy controls and are positioned in between these two groups.…”
Section: Bd-iimentioning
confidence: 74%
“…With regard to general intellectual function, these meta-analyses report that there is no difference between BD-II and healthy subjects neither in the estimated current intelligence quotient (IQ) nor the premorbid IQ (Sole et al 2011. Concerning specifi c neurocognitive functions, one meta-analysis reported that with the exception of memory and semantic fl uency, cognitive impairment in BD-II patients is as severe as in BD-I patients (Bora et al 2011 ).…”
Section: Bd-iimentioning
confidence: 99%
“…Intellectual functioning was intact. A recent review of the literature [57] shows deficits in working memory and some aspects of executive functions (inhibitory control).…”
Section: Cognitive Functions In Bipolar Patientsmentioning
confidence: 99%